Journalism in Portugal: Paquete de Oliveira's contribution to the characterization of the profession and the portrait of journalists today - Crespo, Miguel (2017)
If today it is possible to understand the changes in journalism in Portugal, which are evident in the studies carried out over the last three decades, this is due to the pioneering work of José Manuel Paquete de Oliveira. The singularity of his research work in this field lies in his attention to the observation of the social dynamics of journalism and the understanding of the social role of the journalist as gatekeeper of citizenship. Thanks to its contribution, after 30 years, it is possible to make a transversal and longitudinal sociographic portrait of journalism in Portugal.To characterize who the Portuguese journalists are, we analyzed several studies were carried out between 1987 and 2016 in order to obtain a longitudinal analysis of the profile of the journalists and to reflect on a set of questions that guided the research of Paquete de Oliveira, namely the social role of Journalism in Portugal, and its contribution to a free, plural and democratic society.This reflection, which does not intend to prevent further analyzes on journalists and journalism, focuses on some of the main issues that concern the professionals today, and concerned Paquete de Oliveirathree decades ago. In addition to characterizing the professionals, we analyze their geographic concentration and their investment in learning and professional training.